PECULIARITIES OF SPORADIC ES LAYER IN THE PERIOD OF SOLAR CYCLE ACTIVITY MAXIMUM - Kravetz, R. O.; Galanin, V. V. (Одеські астрономічні публікації, 2013)
We consider the year and a half row of observed ionosphere data from European ionosonde network DIAS in the period of 24 solar cycle activity maximum. The season changes of the mean critical frequency of sporadic Es layer are determined. We show that the frequency of appearing of this layer in summer months is essentially exceeding it frequency of appearing in the winter ones. We compare critical frequency of Es layer with the critical frequency of F2 layer. ionosphere; ionogram